Synthesis, Characterization And Properties Of Silver Nanoparticles And Silver/Polyaniline Nanocomposites - Rajasingam, Ratnamalar (2015)
Silver/polyaniline (ag/pani) nanocomposites are promising materials due to improved properties enabling various applications to date. In this work, a comparative study on the citrate reduction of silver nanoparticles (agnps) was carried out to investigate the combinations of trilithium citrate (tc) along with ascorbic acid (aa) and d-sorbitol (ds) in reducing silver nitrate (sn). The influence of varying concentrations of precursors, time, and temperature conditions towards diffraction (xrd), ultraviolet/visible spectroscopy (uv-vis), transmission electron microscopy (tem), and field emission scanning electron microscopy (fesem). The characterization results showed that increasing concentrations of sn and aa yielded increasing sizes of agnps, but vice versa for the addition concentrations of tc and ds. The xrd patterns confirmed distinct peaks at approximately 20 = 38.2, 44.4, 64.6, 77.6, and 81.7°, representing bragg’s reflections from the (111), (200), (220), (311), and (222) planes of the face-centred cubic lattice phase of metallic silver while the uv-vis results recorded surface plasmon resonance in ranges of 414-452nm.